Investment Decision Behaviour of Nepalese Investors in Initial Public Offerings - Tamang, Puja (Journal of Business and Social Sciences Research, 2022)
The main objective of this study is to explore the investment decision behaviour of Nepalese investors in Initial Public Offerings (IPOs). The study is qualitative in nature where semi-structured interviews are adopted to solicit an understanding of six young Nepalese investors on their investment decision. An understanding of how a specific individual in a specific setting makes meaning of a specific experience has been gained through the application of interpretative phenomenological analysis. The findings indicate investors are not influenced by psychological biases because they do not ‘herd’ on the information; rather it was found that they are influenced by overconfidence bias as investors overestimate their skills when investing. Moreover, this study has solely focused on IPO only, i.e., primary market, further qualitative research can be conducted on the secondary market to understand the financial setting and gain knowledge on how investors behave when investing in a riskier and more volatile market.